A Evaluation of Industrial Work Practice Programs in Expertise Program of Machanical Engineering in Vocational High School 1 West Sumatera in 2018 - Rusdi Sahara; M. Giatman; Mulianti Mulianti (Postgraduate School, Universitas Negeri Padang, 2019)
This study aims to evaluate the implementation of the Industrial Work Practices program at SMK Negeri 1 West Sumatra. The evaluation of the Industrial Work Practices (Prakerin) program was seen from the aspects of design, installation, procurement, product and cost faced in the implementation of the Prakerin program. The research method used is a combination of Sequental Explanatory design methods, combining sequential and qualitative research methods in sequence, which in the first stage of research uses quantitative methods and in the second stage qualitative methods. The results showed that the implementation of Industrial Work Practices in the West Sumatra Vocational High School 1 Mechanical Engineering program as a whole included: Evaluation of designs according to reality obtained a standard average score of 72% enough, and design evaluation as expected obtained a standard average score of 85.4 % well. In reality, the evaluation of the installation obtained an average standard score of 74.5% is sufficient, and the evaluation of the appropriate expectations obtained a standard average score of 85.5% good. Process evaluation according to reality obtained a standard average score of 75.4% enough, and Process evaluation in line with expectations obtained a standard average score of 84.6%. Product evaluation according to reality gets an average standard score of 66.1% enough, and Product evaluation according to expectations gets an average standard score of 83.6% enough. Cost Evaluation according to the fact that the standard score average is 72.9% is sufficient, Cost evaluation according to expectations gets a standard average score of 84.2% is enough. Based on the findings of this study, it was concluded that the Industrial Job Training program (Prakerin) in the 2018 SMKN 1 Sumatera Barat Mechanical Engineering skills program was still in the sufficient category, needing to be improved for each aspect.